2020
DOI: 10.1371/journal.pntd.0007979
|View full text |Cite
|
Sign up to set email alerts
|

High risk for human exposure to Rift Valley fever virus in communities living along livestock movement routes: A cross-sectional survey in Kenya

Abstract: IntroductionMultiple outbreaks of Rift Valley Fever (RVF) with devastating effects have occurred in East Africa. These outbreaks cause disease in both livestock and humans and affect poor households most severely. Communities living in areas practicing nomadic livestock movement may be at higher risk of infection. This study sought to i) determine the human exposure to Rift Valley fever virus (RVFV) in populations living within nomadic animal movement routes in Kenya; and ii) identify risk factors for RVFV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…In addition, an increase in seroprevalence is to be expected in longer-lived species, such as humans, even if the force of infection is relatively stable over time, due to the accumulation of exposed individuals who survived infection (i.e., seropositive individuals). Age-stratified sampling could help disentangle these historical transmission patterns [64], but few studies reported on the age of participants and fewer provided age-stratified data (for examples, see [65][66][67]). In addition, structured, long-term seroconversion studies that include both humans and main animal hosts could help provide local evidence of the force of infection and how it changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in seroprevalence is to be expected in longer-lived species, such as humans, even if the force of infection is relatively stable over time, due to the accumulation of exposed individuals who survived infection (i.e., seropositive individuals). Age-stratified sampling could help disentangle these historical transmission patterns [64], but few studies reported on the age of participants and fewer provided age-stratified data (for examples, see [65][66][67]). In addition, structured, long-term seroconversion studies that include both humans and main animal hosts could help provide local evidence of the force of infection and how it changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…seropositive individuals). Age-stratified sampling could help disentangle these historical transmission patterns [64], but few studies reported on the age of participants and fewer provided age-stratified data ( but, for examples see [65][66][67]). In addition, structured, long-term seroconversion studies that include both humans and main animal hosts could help provide local evidence of the force of infection and how it changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in seroprevalence is to be expected in longer-lived species, like humans, even if the force of infection is relatively stable over time, due to the accumulation of exposed individuals who survived infection (i.e., seropositive individuals). Age-stratified sampling could help disentangle these historical transmission patterns [64], but few studies reported on the age of participants and fewer provided age-stratified data (but, for examples see [6567]). In addition, structured, long-term seroconversion studies that include both humans and main animal hosts could help provide local evidence of the force of infection and how it changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that among studies that were technically excluded from our review, there were several completely negative serosurveys of animals performed in Spain [51], the Canary Islands [52], Mauritius [158], Zanzibar [159], South Korea [54], and Poland [53]. Expansion of RVFV transmission has been aided by livestock movement [34,[160][161][162][163] and the increasing frequency of extreme weather events involving heavy rainfall and flooding [59]. The discovery of vertical transmission within insect vector species other than floodwater Aedes spp.…”
Section: Evidence Of Vector Presence and Competence For Interepidemic Rvfvmentioning
confidence: 99%